Low Serum Magnesium in Acute Ischemic Stroke Patients: Correlations with the National Institutes of Health Stroke Scale Scores - Jaiprakash Kuldeep; Konika Jain; Chandrakant Salve (APIK Journal of Internal Medicine)
Introduction: Stroke profoundly impacts global health, particularly in developing countries, and is a leading cause of death and disability. This study explores the serum magnesium (Mg) concentration in acute ischemic stroke patients on hospital admission, aiming to uncover the correlation between Mg levels and the severity of stroke, as quantified by the National Institutes of Health Stroke Scale (NIHSS). The aim of this study was to analyze the correlation between serum Mg levels and acute ischemic stroke severity as measured by NIHSS scores. Materials and Methods: We assessed 100 acute ischemic stroke patients and 100 controls over 2 years in an observational study. Serum Mg levels were measured on the day of admission and on Day 3 and were compared to those of a control group. Results: The analysis showed that stroke patients had significantly lower serum Mg levels at admission (1.79 ± 0.54 mg/dl) compared to the control group (2.02 ± 0.48 mg/dl, P = 0.002), as well as on Day 3 (1.98 ± 0.52 mg/dl vs. 2.19 ± 0.40 mg/dl, P = 0.001). Higher NIHSS scores were associated with lower Mg levels, suggesting Mg deficiency in these patients. Conclusion: On observing the close correlation between low serum Mg levels and a greater severity of ischemic strokes, this study emphasizes the prognostic relevance of Mg. The findings prompt further research into optimal approaches for Mg-based interventions in stroke care.